2020
DOI: 10.1186/s12875-020-01287-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of family doctor contract services on patient perceived quality of primary care in southern China

Abstract: Background Family doctor contract service is an important service item in China’s primary care reform. This research was designed to evaluate the impact of the provision of family doctor contract services on the patient-perceived quality of primary care, and therefore give evidence-based policy suggestions. Methods This cross-sectional study of family doctor contract service policy was conducted in three pilot cities in the Pearl River Delta, South China, using a multistage stratified sampling method. The va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Chinese residents, especially those with poor health status, have very few trust in competences of primary care providers; thus, they would seek health-care resources directly from hospitals once they get sick. Individuals with family doctor contracts have better access to and spend more time with preferred general physicians, which improve their perceived primary care quality and benefits in satisfaction and trust in PCIs [ 54 ]. The signing coverage rate in China of family doctor’s contract is still very low after the FDCS was launched in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese residents, especially those with poor health status, have very few trust in competences of primary care providers; thus, they would seek health-care resources directly from hospitals once they get sick. Individuals with family doctor contracts have better access to and spend more time with preferred general physicians, which improve their perceived primary care quality and benefits in satisfaction and trust in PCIs [ 54 ]. The signing coverage rate in China of family doctor’s contract is still very low after the FDCS was launched in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The residents were encouraged to use family doctor services, such as priority referral appointments, convenient medications, targeted health management, medical insurance management and other supporting services, in order to gradually establish a hierarchical medical system and to fully realize the gatekeeper role of family doctors. [12][13][14] Due to the lack of qualitative systematic summaries and quantitative evaluations in the existing studies, this study aimed to summarize the experience of the promotion of the scheme of signings with family doctors in Shanghai and to evaluate its effectiveness. When regarding the promotion of family doctor services in China, Shanghai is far ahead of other cities in China; however, the circumstances commonly involve the idea that patients can freely choose the type of primary care and specialist without strict restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the family practice contract services’ policy can improve the process quality experience of patients [ 39 , 40 ], but it is not clear whether this policy has an equivalent effect on perceived care quality among patients with multiple chronic diseases, with a single chronic disease and with no chronic diseases and whether patients with multiple chronic diseases can benefit to a greater extent than those among the other two groups.…”
Section: Introductionmentioning
confidence: 99%